2021
DOI: 10.22271/oral.2021.v7.i1f.1166
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Canalis sinuosus prevalence by cone beam computed tomographs (CBCT)

Abstract: The aims of this study were to map the main locations of Canalis sinuosus (CS), to (i) identify accessory foramina in the hard palate region, (ii) indicate the prevalence, and (iii) view them when using CBCT images. A sample of 230 cone-beam computed tomography (CBCT) examinations was obtained. The CBCT images that were generated by a multiplanar reconstruction of the axial and/or coronal planes were evaluated by On Demand 3D™ Dental software. The prevalence of Canalis sinuosus was 224 (97.4%). The examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…One study 27 did not explain how the diameter was measured while other retrospective studies did not investigate diameter. 25,36,38,42,43,[49][50][51][52][53][54] There are only two reports on the presence of more than two CS (one in each quadrant) in a patient. The present study corroborates with von Arx et al 22 and Sekerci et al 34 where 4.08% and 3.3%, respectively, had three CS, while 0.56% and 0.8% of the above studies reported four CS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study 27 did not explain how the diameter was measured while other retrospective studies did not investigate diameter. 25,36,38,42,43,[49][50][51][52][53][54] There are only two reports on the presence of more than two CS (one in each quadrant) in a patient. The present study corroborates with von Arx et al 22 and Sekerci et al 34 where 4.08% and 3.3%, respectively, had three CS, while 0.56% and 0.8% of the above studies reported four CS.…”
Section: Discussionmentioning
confidence: 99%
“…were the only two studies that measured diameter of CS using the sagittal plane but an explanation for this was not given. One study 27 did not explain how the diameter was measured while other retrospective studies did not investigate diameter 25, 36, 38, 42, 43, 49–54 …”
Section: Discussionmentioning
confidence: 99%
“…The presence of canalis sinuosus based on CBCT examinations was assessed (Tables 1 and 2). The outcome of the literature review demonstrated that the presence of CS was 54.44% (Figure 3), the presence of CS among women was 56.76%, and men 43.24% (on the basis of 11 articles, in which the division on men and women was included) [3,5,8,11,19,[20][21][22][23][24][25]. In a total of 8 researches, the unilateral CS was observed in 41.78%, whereas bilateral CS was found in 58.22% CBCT images [3, 5, 8, 21-23, 25, 26].…”
Section: Resultsmentioning
confidence: 99%
“…In four studies, in which the overall occurrence of CS was 100%, it was also more frequently observed in women [3,[19][20][21]. The relationship between the occurrence of CS and age of the examined patients was analyzed in 4 out of 12 studies [5,[22][23][24]. Aoki et al [5] tested patients aged 18 to 85 years, with a median age of 53 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation